Biodegradation of Ammonia from Polluted Water using a Biofilters Inoculated with Klebsiella pneumoniae and Bacillus cereus: A Case Study of the Musi River, Indonesia - Jeni Meiyerani; Melki; Hary Widjajanti; Rozirwan Rozirwan; Riris Aryawati (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2026)
High concentrations of ammonia in rivers can cause water pollution through eutrophication. It is necessary to reduce ammonia in an environmentally friendly manner using biofilters, such as zeolite. Water samples from the Musi River, South Sumatra, were collected from six stations, namely Palembang City (Gandus, AMPERA, PUSRI) and Banyuasin Regency (Marga Sungsang, Sungsang II, Sungsang IV). The biofilter was designed to combine physical filtration using filter media such as activated carbon, anthracite, ferrolite, silica sand, and zeolite with biodegradation by nitrifying bacteria. The controls were treated in the same manner as the other samples, without the addition of the bacterial combination. The best decomposing bacteria were determined based on the reduction in ammonia and nitrite levels in the water. Over 14 days, the system achieved a 68.92% reduction in ammonia concentration. The nitrite levels were effectively maintained below 0.063 mg/L throughout the process. Evaluation of the optimal bacterial consortium (Sample C2) showed a significant improvement in key water quality parameters: pH decreased from 8.1 to a more neutral 6.5, while dissolved oxygen increased significantly from 5.4 to 9.42 mg/L, indicating improved aerobic conditions. Molecular identification revealed Klebsiella pneumoniae and Bacillus cereus as the ammonia- and nitrite-degrading bacteria, respectively. The biofiltration system canreduce ammonia pollution and improve river water quality at the laboratory scale.